Three-Dimensional 3D Culture Models in Gynecological and Breast Cancer Research - Salinas-Vera, Yarely M.; Valdés, Jesús; Pérez-Navarro, Yussel; Mandujano-Lazaro, Gilberto; Marchat, Laurence A.; Ramos-Payán, Rosalio; Nuñez-Olvera, Stephanie I.; Pérez-Plascencia, Carlos; López-Camarillo, César (Frontiers in Oncology, 2022)
Traditional two-dimensional (2D) monolayer cell cultures have long been the gold standard for cancer biology research. However, their ability to accurately reflect the molecular mechanisms of tumors occurring in vivo is limited. Recent development of three-dimensional (3D) cell culture models facilitate the possibility to better recapitulate several of the biological and molecular characteristics of tumors in vivo, such as cancer cells heterogeneity, cell-extracellular matrix interactions, development of a hypoxic microenvironment, signaling pathway activities depending on contacts with extracellular matrix, differential growth kinetics, more accurate drugs response, and specific gene expression and epigenetic patterns. In this review, we discuss the utilization of different types of 3D culture models including spheroids, organotypic models and patient-derived organoids in gynecologic cancers research, as well as its potential applications in oncological research mainly for screening drugs with major physiological and clinical relevance. Moreover, microRNAs regulation of cancer hallmarks in 3D cell cultures from different types of cancers is discussed.